2016
DOI: 10.3791/53800
|View full text |Cite
|
Sign up to set email alerts
|

Determining Pain Detection and Tolerance Thresholds Using an Integrated, Multi-Modal Pain Task Battery

Abstract: Human pain models are useful in the assessing the analgesic effect of drugs, providing information about a drug's pharmacology and identify potentially suitable therapeutic populations. The need to use a comprehensive battery of pain models is highlighted by studies whereby only a single pain model, thought to relate to the clinical situation, demonstrates lack of efficacy. No single experimental model can mimic the complex nature of clinical pain. The integrated, multi-modal pain task battery presented here e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 20 publications
(20 reference statements)
3
32
0
Order By: Relevance
“…Pregabalin and ibuprofen were used as positive controls. Previous studies performed at our center with the same study design demonstrated consistent results, with ibuprofen significantly decreasing the pain threshold for heat pain on UVB exposed skin, and pregabalin significantly decreasing the pain thresholds for pressure stimulation and the cold pressor test …”
Section: Methodssupporting
confidence: 75%
See 3 more Smart Citations
“…Pregabalin and ibuprofen were used as positive controls. Previous studies performed at our center with the same study design demonstrated consistent results, with ibuprofen significantly decreasing the pain threshold for heat pain on UVB exposed skin, and pregabalin significantly decreasing the pain thresholds for pressure stimulation and the cold pressor test …”
Section: Methodssupporting
confidence: 75%
“…Nociceptive and inflammatory pain was assessed by means of the heat and inflammatory heat pain assessments, electrical stimulation assessment, cold pressor assessment, and the pressure stimulation assessment. Detailed descriptions of the models have been described previously . Assessments were conducted predose and 0.5, 1, 2, 3, 4, 6, 8, and 10 hours postdose by trained personnel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacodynamics was measured using an integrated battery of pain models designed to measure various modalities of pain. These models have been described previously (Hay et al, ), and all assessments were performed by trained personnel. In all four studies, tasks were performed in order to measure the pain detection threshold (PDT) and the pain tolerance threshold (PTT).…”
Section: Methodsmentioning
confidence: 99%